Analysis Factor that Affecting to the Family Abilities in Treating Patients of Mental Disorders at Community Health Centers Teja Pamekasan - Fatimatur Rahmaniyah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
One of the obstacles in the healing of mental patients is the knowledge of the community and the family. Usually society and family, treatment of mental disorders patients brought to the paranormal. The purpose of this study is to analyze factors that affect the ability of families in caring for people with mental disorders. This research is a quantitative research with observational analytic design cross sectional approach. This study was conducted on February 2018 at Puskesmas Teja Pamekasan with a family of households living in a house with mental disorders of 97 families. A sample size of 87 families. The independent variables are knowledge, family support, and family burden. Dependent variable is the ability of families in caring for people with mental disorders. Data were analyzed using logistic regression test with P = 0.05. The results showed that the variable of knowledge with p = 0,646; OR = .798, family support variable with p = 0.010; OR = 6.028, variable of family load with p = 0,313; OR = 1.688 so it can be concluded that the most dominant factor is family support factor with influence of 6.028. Less of family support making the lack of family ability to care people with mental disorders, so that the efforts of promoting and counseling the family in terms of how to care for people with mental disorders with counseling and home visits so that government programs can be achieved optimally.